Does Empirical Antibiotic Use Improve Outcomes in Ventilated Patients with Pandemic Viral Infection? A Multicentre Retrospective Study - Elisabeth Papiol; Julen Berrueta; Juan Carlos Ruíz-Rodríguez; Ricard Ferrer; Sara Manrique; Laura Claverias; Alejandro García-Martínez; Pau Orts; Emili Díaz; Rafael Zaragoza; Marco Marotta; María Bodí; et al. (Antibiotics, 2025)
Background: During the influenza A(H1N1) and COVID-19 pandemics, empirical antibiotic treatment (EAT) was widely administered to critically ill patients despite low rates of confirmed bacterial co-infection (COI). The clinical benefit of this practice remains uncertain and may contradict antimicrobial stewardship principles. Objective: To evaluate whether EAT at ICU admission reduces ventilator-associated pneumonia (VAP) incidence or ICU mortality in critically ill patients with pandemic viral pneumonia, stratified by presence of COI. Methods: This retrospective analysis combined two national multicentre ICU registries in Spain, including 4197 adult patients requiring invasive mechanical ventilation for influenza A(H1N1) or COVID-19 between 2009 and 2021. Primary outcomes were ICU mortality and VAP incidence. Analyses were stratified by microbiologically confirmed bacterial COI. Propensity score matching, Cox regression, General Linear (GLM), and random forest models were applied. Results: Among patients without COI (n = 3543), EAT was not associated with lower ICU mortality (OR = 1.02, 95%CI 0.81–1.28, p = 0.87) or VAP (OR = 1.02, 95%CI 0.79–1.39, p = 0.89). In patients with confirmed COI (n = 654), appropriate EAT was associated with reduced VAP (17.4% vs. 36.3%, p < 0.001) and ICU mortality (38.4% vs. 49.6%, OR = 1.89, 95%CI 1.13–3.14, p = 0.03) compared to inappropriate EAT. Conclusions: EAT was not associated with a lower incidence of VAP or higher survival rates and could be harmful if administered incorrectly. These findings support a more targeted approach to antibiotic use, guided by microbiology, biomarkers and stewardship principles.